DIAGNOSTICS AND PLANNING OF ORTHODONTIC TREATMENT OF PATIENTS WITH DENTAL ARCH NARROWING USING 3D TECHNOLOGIES - Yu.M. Voliak; Z.R. Ozhohan (Ukrainian Medical Stomatological Academy, 2015)
According to some authors, dentofacial abnormalities occur in 33.7% - 74.0% on average manifesting in maxilla narrowing and teeth crowding in cases of lack of spaces in the dental row and are characterized by decrease in longitudinal length of dentition. Anthropometry is the main method of recognition of bite formation processes and orthodontic treatment planning. Adherence to sequence that is to performance algorithm is essential in metric researches. In addition to anthropometry, radiological method is also one of the main methods of examination in orthodontia. We have studied dental panoramic radiography (DPR) and lateral teleroentgenograms. DPR of jaws gives a perspective of the number and location of immature teeth, enables the assessment of space for yet unerupted teeth and the study of a number of crowns, their size and shape, angle of their inclination. The study of lateral teleroentgenograms is the most informative way to identify structural features of facial skull. It allows specifying craniometric, gnathometric and profilometric sizes accounting of which helps determine the indications and contraindications to the method of dentofacial abnormalities treatment. Clarification of the early signs of the pathology is judged from the main principle of diagnosis, namely determining the symptoms according to their clinical signs and their comparison with norm signs. The rapid development of CAD/CAM dentistry including computer systems of orthopedic and orthodontic structures manufacturing allowed us to use modern 3D-technologies for diagnosis and further orthodontic treatment of patients with dental arch narrowing. The objective of the research was to increase the effectiveness of diagnosis and orthodontic treatment of patients with dental arch narrowing combined with ENT diseases using 3D technologies. Materials and methods We observed 35 children at the age of 9 to 14 using both basic diagnostic methods and additional (special) diagnostic methods. Using clinical examination methods we paid attention to appearance, clinical signs indicating maxilla narrowing and absence of nasal breathing. Method of 3D scanning of stone models was used as additional (special) method of jaw narrowing diagnosis. Obtained three-dimensional jaw models were subjected to computer processing using editor program of three-dimensional models 3SHAPE. 3SHAPE is a powerful means of three-dimensional scanning data processing. We used both calipers and 3SHAPЕ program on three-dimensional models to measure the models. It is not necessarily to keep numerous stone models to create an archive data of orthodontic patients before and after treatment. They can be simply stored in 3D-format on personal computer. Obtained three-dimensional model was used both for initial abnormalities of dentition development and for designing of each tooth movement. Results of the research Using 3D models of jaws we may plan the way of some teeth displacement so that to put them to a new correct position. Three-dimensional virtual model of teeth may be shifted in any direction, namely mesial, distal, palatal, lingual, rotationally along the tooth axis, etc. with the use dimensional editor program. According to our proposed method comprehensive treatment of patients with dental arch narrowing and ENT diseases was conducted and the following results were obtained. Indices of maxilla width in the area of the first premolars constituted 32.29+2.8 millimeters before the treatment which included treatment of ENT pathology and maxilla expansion. After treatment they significantly (р< 0.05) increased to 38.42+2.2 millimeters. Similar dynamics was observed taking into account the maxilla width in the area of the first molars. This index constituted 42.51+3.0 millimeters before the treatment and significantly increased to 49.45+2.18 millimeters after the treatment. We determined that palatal height in the area 6|6 decreased from 18.51+0.7 millimeters to 15.53+0.81 millimeters after the maxilla expansion. Korkhaus' Index increased (р<0.05) from 18.64+0.27 millimeters to 19.47+0.21 millimeters after treatment. Conclusions Thus, 3D analysis of models, the proposed technique of measuring and modeling of the clinical situation provide us with a range of advantages over the traditional method of models diagnosis. These advantages include measurement accuracy, reduces number of stone models, the possibility of an archive creating, ease in finding the right model, durability of model storage, better visualization and it does not occupy a lot of space. The use of the proposed method of complex diagnosis and treatment of patients with maxilla narrowing and ENT pathology in mixed bite allows to obtain significantly better (p<0.05) indicators of maxilla width.